The Effectiveness of Group-Based Dialectical Behavior Therapy in Aggression and Social Adjustment of Single-Parent Adolescents - Nazarifar, Mohsen; Savari , Hadi; Kalalian Moghaddam, Hamid (Shahroud Journal of Medical Sciences, 2022)
Background: The absence of each parent impairs the psychological and the social adjustment of single-parent adolescents. The objective of this study was to investigate the effectiveness of group-based dialectical behavior therapy in reducing aggression and increasing social adjustment of single-parent adolescents. Methods: The research method was quasi-experimental using a pretest and posttest design with a control group. The statistical population included single-parent adolescent boys in the junior high schools of Baghmalek. The sample consisted of 24 students who were randomly assigned to the experimental and the control groups. The experimental group received dialectical behavioral therapy during eight sessions. The research instruments included Ahwaz Aggression Questionnaire (AAI) and Bell’s Adjustment Inventory (BAI). Data were analyzed using descriptive statistics (mean and standard deviation) and inferential statistics (multivariate analysis of covariance). Results: Findings showed that group-based dialectical behavior therapy reduced aggression and increased social adjustment of the experimental group compared to the control group (p < 0.05). In fact, the results showed the effect of dialectical behavior therapy in reducing aggression and improving social adjustment in single-parent adolescents. Conclusion: According to the research results, counselors and psychotherapists can use dialectical behavior therapy to intervene aggression and social adjustment. Keywords: Dialectical behavior therapy, Aggression, Social Adjustment, Single-parent adolescents